The Relationship Between Eye Distance To The Computer And Computer Vision Syndrome (CVS) Complaints - Alfa Sylvestris; Salma Nurisna Ulfairoh; Bragastio Sidharta (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2023)
The use of computers is now commonplace among individuals, ranging from students to professionals. Computers offer numerous advantages, leading to a high dependency on them, particularly among office workers, who incorporate computer usage into their daily activities. In general, the occupational setting necessitates prolonged computer usage, thereby leading to inadvertent exposure to the computer screen/monitor and subsequent development of eye-related complaints, including Computer Vision Syndrome (CVS). This study aimed to investigate the correlation between eye distance to the computer and the occurrence of CVS symptoms. This research employs an analytical observational study design with a cross-sectional approach. The study sample consists of employees from the Middle Type Customs and Excise Service Office (KPPBC TMC) in Malang. The sample selection was based on the prolonged duration of computer usage, averaging 6 hours per working day. The study findings indicated a significant correlation between the viewing distance to the computer screen and the occurrence of CVS complaints among the respondents. Among the total of 65 respondents, 66.2% experienced CVS complaints, with the most predominant symptom being tired eyes at 53.8%. A higher proportion of respondents (53.8%) had an eye distance from the computer of less than 50 cm, compared to those with an eye distance of more than 50 cm (46.2%). The majority of respondents in this study were in the age range of 25-29 years, comprising 40% of the sample. Among them, the majority were male, accounting for 57.7% of the respondents.